TRIAL RITUALS IN MOROCCO: ATTEMPTING TO UNDERSTAND THE REPRESENTATIONS AND EXPLICITNESS OF MODERNISATION CHOICES - Anouar Hatim (Center of Middle Eastern Studies (CMES), 2023)
This research aims to retrace and interpret the symbolic representations of trial rituals inherited from colonial times in North African countries, attempting to recycle them and make them more compatible with the principles of justice and fairness on which each trial is based. To this end, the researcher used a qualitative descriptive approach, which involved presenting the research problem, collecting the relevant data and analysing it before drawing conclusions. The research has produced several findings, the most important of which is that the symbolic framework of the trial, while helping to present the authority and legitimacy of justice, is in contrast to the values of justice, fairness and equality between the adversaries. It tends to condemn the still innocent accused, even practising intentional violence and ritually contaminating his identity by the insinuations and innuendoes it practices.